PSYCHOSOCIAL DETERMINANTS OF PHYSICAL ACTIVITY AMONG PUBLIC SECTOR LIBRARIANS: A CROSS-SECTIONAL STUDY IN BRUNEI DARUSSALAM - Amirul Rahman; Nik AA Tuah; Hanif Abd Rahman (Universitas Airlangga, 2025)
Background: Physical inactivity is a leading global health risk, with 31% of adults worldwide not meeting recommended activity levels, yet evidence on psychosocial determinants among sedentary professionals remains limited. Aims: To examine psychosocial determinants of physical activity and their associations with socio-demographic characteristics. Methods: A cross-sectional survey was conducted in May to June 2025 among 153 librarians. Data were collected using a validated psychosocial and behavioural PA questionnaire informed by established psychosocial theories. Descriptive statistics and multiple linear regression were conducted to examine the associations between demographic variables and psychosocial determinants, with P value of < 0.05 considered statistically significant. Results: Librarians reported moderate self-efficacy, behavioural intention, leisure-time PA, and workplace PA, with high perceived benefits and response efficacy. Female librarians had significantly lower self-efficacy (β = -0.43, p = 0.023), behavioural intention (β = -21.56, p = 0.001), and workplace PA (β = -0.50, p = 0.007) than males. Older groups perceived fewer benefits (β = -0.74 to -0.53, all p < 0.05) and lower inactivity severity (β = -0.72, p = 0.023). Higher education was unexpectedly linked with lower perceived vulnerability (β = -0.39, p = 0.046) and weaker intention (β = -8.70, p = 0.031). Officer-level librarians reported higher leisure-time PA (β = 8.59, p = 0.042) and workplace PA (β = 0.46, p = 0.003) than support staff. Conclusion: Socio-demographic characteristics shaped psychosocial determinants and PA behaviours among librarians. Tailored interventions should be considered. Findings may extend to other sedentary ISCO-08 occupations.